Sperm cell capacitation status of ram semen after cooling - Bartmer, Monica Elisa (2022)
Background: The use of conventional artificial insemination (AI) in sheep production is usually associated with lower fertility rates when frozen semen is used. Cooled ram semen has been an alternative over frozen semen due to the higher viability, seminal quality and fertility rates following AI. The semen preservation process promotes sperm cell modifica¬tions similar to capacitation (capacitation-like) that causes cell damage affecting viability and seminal quality, but such effects are unclear for cooled semen. The aim of this study was to determine the status of sperm cell capacitation (CA) and acrosome reaction (AR) during ram semen processing and cooling under different extenders, dilution factors, and aerobiosis conditions as a function of storage time at 5oC. Materials, Methods & Results: Two consecutive ejaculates per day per male were collected from 2 adult rams by artifi¬cial vagina at 48-72 h intervals, in three replications. After macro- and microscopic evaluations, semen was segregated into groups under 3 extenders (Tris-egg yolk or TY, citrate-egg yolk or CY, skimmed milk or SM), 2 dilution factors (1 x 109 or Bi, 100 x 106 or Mi cells/mL), and 2 aerobiosis conditions (aerobic or A, semi-anaerobic or SA). Diluted semen was cooled to 5ºC and stored for up to 72 h, with evaluations every 24 h. Aliquots of fresh ejaculates and of each cooled diluted subgroup, according to extender, dilution, and aerobiosis, were collected at times T0 and T72 for determination of acrosome status and membrane integrity by the chlortetracycline (CTC) and trypan blue-Giemsa stainings, respectively. No differences were detected in sperm cell motility (M) and motility vigor (V) between fresh and diluted semen. After cooling, a significant decrease in M was observed after 48 h in CY and SM compared with fresh semen and 0 h of cool¬ing, while V started to decrease after 24 h in CY compared with TY. Likewise, M/V from different dilutions and aerobic conditions decreased more significantly after 48 and 24 h of cooling, respectively. The sperm capacitation status did not show differences in the proportion of non-capacitated (NCA), CA and AR sperm cells between TY, CY, and SM extend¬ers (NCA: 75.0%, 71.3%, 74.0%; CA: 15.7%, 17.2%, 15.9%; AR: 9.3%, 11.5%, 10.2%) or between Bi and Mi dilutions (NCA: 74.0%, 72.9%; CA: 15.9%, 16.6%; AR: 10.1%, 10.5%), respectively. However, differences (P < 0.05) were observed between A and SA aerobic conditions, with CA (17.0% vs. 15.5%) and AR (11.9% vs. 8.7%) rates being higher in A than SA, respectively, with no differences in NCA (71.1% vs. 75.8%), irrespective of the storage time. Sperm cell viability decreased after 48 h, especially in CY (P < 0.05). Discussion: Ram sperm cells can suffer irreversible damage due to thermal shock during cooling. Egg yolk-based extend¬ers provide phospholipids and cholesterol to protect the sperm cell membrane during the thermal shock caused by the change in temperature. In this study, sperm cells had irreversible decreases in M/V, with increase in acrosome and plasma membrane damage after cooling to 5ºC. The largest and smallest decreases in M and V over time were observed in the CY and TY extenders, respectively. In addition to the extender type, the semen preservation method and storage time promoted changes in the capacitation status, AR and in sperm cell viability, which per se were associated with a decrease in semen fertility. In fact, the proportions of CA and/or AR sperm cells gradually increased over time after dilution and storage at 5ºC, with a negative correlation between sperm cell viability and M/V over time. In summary, extender and cooling time affected mostly M/V, while aerobiosis condition and dilution factor were more associated with acrosome status and sperm survival, with the extender having less impact on the acrosome status as a function of time.